Portrait of Louis XV of France - Engraving 18th century - Laurent Cars / After... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Portrait of Louis XV of France - Engraving 18th century. Engraved portrait of Louis XV of France
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons